2022
DOI: 10.3390/su14148510
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Storage Assessment: Using Frequency Modulation Approach to Capture Optimal Coordination

Abstract: To reduce the allocation of energy storage capacity in wind farms and improve economic benefits, this study is focused on the virtual synchronous generator (synchronverter) technology. A system accompanied by wind power, energy storage, a synchronous generator and load is presented in detail. A brief description of the virtual synchronous generator control strategy is given. The capacity allocation is based on different optimization goals and the optimal energy storage capacity configuration of the coordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…It is assumed that N buildings with several houses make up the user layer. All residences are equipped with an RER and an energy storage system (ESS) for meeting energy demands [ 24 , 25 ]. It is environmentally friendly and does not emit pollutants due to the fact that the energy is derived from natural resources.…”
Section: System Schemementioning
confidence: 99%
“…It is assumed that N buildings with several houses make up the user layer. All residences are equipped with an RER and an energy storage system (ESS) for meeting energy demands [ 24 , 25 ]. It is environmentally friendly and does not emit pollutants due to the fact that the energy is derived from natural resources.…”
Section: System Schemementioning
confidence: 99%
“…It is anticipated that the generation of wind energy using OWFs can be nearly 54 GW in the United States [5]. The technical complexities associated with the implementation of offshore platforms and the process of transferring power from OWF to onshore power grids needs significant attention [6][7][8]. Previous studies have shown that the HVDC transmission is superior to HVAC transmission in terms of improved technical and economic feasibility, sustainability, and flexibility of integration with larger wind farms located at greater distances [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [7] proposed a wind‐storage coordination optimization strategy to enhance the economic benefits. In order to conquer the uncertainty of renewable sources, ref.…”
Section: Introductionmentioning
confidence: 99%